The Two Banks: Perspectives on Two Recent Operas Premiered in France: Cachafaz by Oscar Strasnoy and Avenida de los Incas 3518 by Fernando Fiszbein. (Revista Argentina de Musicología, 2018)
This paper studies two operas that were recently released in France: Cachafaz, by Oscar Strasnoy, and Avenida de los Incas 3518, by Fernando Fiszbein. Both operas observe the distinction of having plots located in Montevideo and Buenos Aires respectively and being sung in Spanish. The choice of Spanish is also found in other operas written by Argentinean composers in Paris and represents one type of “home marks” of national origin in their work. The compositional strategies are however divergent: Strasnoy makes an intertextual plot in which he combines elements of the opera and milonga music; Fiszbein, instead, keeps the intertextuality out of the musical level. The analysis of these operas is part of a larger project that aims to study Argentine composers who are currently residing in Paris.
Keywords: opera; Argentinean contemporary music; Oscar Strasnoy; Fernando Fiszbein